Uzundara Fortress – The Hellenistic Guardian of Bactria - Gorin Aleksey Nikolayevich (Scientific Trends, 2025)
This article covers the history of the Uzundara fortress and its strategic importance in the Bactrian territory of the Hellenistic period. The author analyzes the role of the fortress in the Border Protection System, defensive architecture and military–political tasks of the Seleucid and Graeco-Bactrian States in the 3rd-2nd centuries BC. Based on archaeological research, the plan of the fortress, the construction technology of its walls and the elements of the fortification are described. The Fort's contribution to ancient urbanization processes and cultural exchanges in Central Asia is also shown. This article is of scientific and practical importance to historians, archaeologists and experts studying cultural heritage.
Keywords: Alexander, Kushan Kingdom